Ancient mitochondrial genomes from the Argentinian Pampas inform the early peopling of the Southern Cone of South America - Roca Rada, Xavier (2021)
The Southern Cone of South America (SCSA) is a key region for investigations about the peopling of the Americas. However, little is known about the eastern sector, the Argentinian Pampas. We analyzed 18 mitochondrial genomes?7 of which are novel?from human skeletal remains from 3 Early to Late Holocene archaeological sites. The Pampas present a distinctive genetic makeup compared to other Middle to Late Holocene pre-Columbian SCSA populations. We also report the earliest individuals carrying SCSA-specific mitochondrial haplogroups D1j and D1g fromEarly andMiddle Holocene, respectively. Using these deep calibration time points in Bayesian phylogenetic reconstructions, we suggest that the first settlers of the Pampas were part of a single and rapid dispersal 15,600 years ago. Finally, we propose that present-day genetic differences between the Pampas and the rest of the SCSA are due to founder effects, genetic drift, and a partial population replacement 9,000 years ago.